Treatment of Covid-19 in a pre-diabetic patient in the intensive care unit: a case report (Research, Society and Development, 2022)
Coronavirus disease (COVID-19) has been widely and globally studied and researched, as it is a new disease with a varied clinical spectrum and its pathophysiology is not completely known. Moreover, the aggravations are associated with the lifestyle and previous diseases of the patients, and the evolution of each patient. Among these problems are obesity and diabetes, diseases that lead to metabolic disorders in the body. The aim of this report is to report the case of a pre-diabetic patient, obese grade II, with infection caused by the Sars-CoV-2 virus and evolution to diabetes during infection, besides presenting secondary physiological repercussions to the infection. The patient studied was diagnosed with Type 2 Diabetes during hospitalization and presented multiple ground-glass opacities with bilateral multifocal distribution on chest computed tomography (CT), so he was referred to the Intensive Care Unit (ICU). In the ICU, he was positive for SARS-Cov-2 by RT-PCR, Orotracheal Intubation was performed, pharmacotherapy was started, and laboratory tests confirmed that the patient is diabetic. In this case, it is notable that because the patient had comorbidities for COVID-19 - pre-diabetes and grade 2 obesity - the disease may have been aggravated by the factors. Thus, he needed pulmonary rehabilitation and intensive care, such as use of medications used in more advanced cases of the disease and ICU monitoring. Therefore, we conclude that it is essential for health professionals to know the clinical picture and pre-existing pathologies of the affected patients, because this data will offer the professional the choice of individualized therapies.